Assessment the impact of climate change on the dryness at Kedah state title - Norosminah, Mohd Ali (2019)
The issue of climate change and its effect on various aspects of the environment has become more challenges for society. It is desirable to analyses and predict the changes of critical climate variables, such as rainfall, temperature and potential evapotranspiration affect in the content of global climate change. This paper assessed the potential dryness index in the long term with considered the impact of the climate changes. To achieve the objective, statistical climate model (SDSM) has been applied to stimulate the changes of the climatic trend at the study area. In this study, the long term climate has been predicted using atmospheric variables which provided by National Centre for Environmental Prediction (NCEP) and General Circulation Model (GCM). Then the Standard Precipitation Index (SPI) used to estimate the dryness index at study area. The dryness index was measured based on the rainfall amount according to cumulative 3-month and 12-month cumulative period. The rainfall amount changed into normal distribution to get a zero SPI mean value for each selected stations and period time scale. The positive value of SPI shows the greater precipitation than median while negative value shows the lesser precipitation than the median. The purpose was to classify the precipitation into dry and wet conditions at Kedah state. Based on the results obtained, SDSM produced good performance in calibration where the average error for all stations was below 20%. Meanwhile, the performance of validation shows the result of error was above 20% but below 40%. The less consistent rainfall historical data at Kedah state given from DID might be the reason for high percentage of error. The rainfall projection at all selected station shows the different prediction compared to historical data. RCP2.6 agreed that Kedah Peak and Kg Gajah Puteh expected to receive lesser annual rainfall compared to historical with 5.58% and 32.92% decrement respectively. All RCPs claim Kg Jelutong expected to receive more rainfall because all RCPs shows increment in predict the future annual rainfall. Meanwhile, RCP8.5 claim Kota Sarang Semut will receive lesser annual rainfall with 7.49% decrement. In order to estimate the dryness index, SPI 3-month and 12-month was analysed for all stations at study area. At least all stations expected to experience three times of extreme dry within the year 2019 until 2040.